2019
DOI: 10.1002/app.47546
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable poly(lactic acid)/cellulose‐based superabsorbent hydrogel composite material as water and fertilizer reservoir in agricultural applications

Abstract: The work presents a fully degradable superabsorbent composite material to be used in agricultural and horticultural applications. It is designed to retain and release fertilizer solutions to the soil in a controlled manner, permitting resource optimization. Because of its ability to absorb and release large amounts of saline water, a natural superabsorbent hydrogel derived from cellulose was chosen. Potassium nitrate was chosen to model the fertilizer. Poly(lactic acid) was added to the final composition in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 17 publications
(16 reference statements)
0
36
0
Order By: Relevance
“…Superabsorbent polymers (SAPs) are hydrophilic polymer networks that are slightly cross‐linked; therefore, they can absorb and retain a huge amount of water, even under pressure . These spectacular absorbency properties candidate SAPs to be employed in various applications, including hygienic products, agriculture, drug delivery systems, and wound dressing . High swelling rate and capacity, along with an acceptable strength of the swollen gel are of common desired features of SAPs .…”
Section: Introductionmentioning
confidence: 99%
“…Superabsorbent polymers (SAPs) are hydrophilic polymer networks that are slightly cross‐linked; therefore, they can absorb and retain a huge amount of water, even under pressure . These spectacular absorbency properties candidate SAPs to be employed in various applications, including hygienic products, agriculture, drug delivery systems, and wound dressing . High swelling rate and capacity, along with an acceptable strength of the swollen gel are of common desired features of SAPs .…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that TA modification could improve the water absorption of the gel due to the excellent hydrophilic and hygroscopicity 47 . Moreover, TA would aggrandize the crosslinking density of the gels, which could improve the steric stability for holding more water in the network 48 . In addition, the swelling ratio increased gradually with the TA content increases from 0.1 g up to 0.3 g, and then decreased considerably with further increases to 0.5 g. The maximum swelling ratio reached to 1179.2 g g −1 when TA content was 0.3 g. There is a possible reason that the proper amount of TA could increase the crosslinking density of gels so as to the swelling ratio increased gradually.…”
Section: Resultsmentioning
confidence: 99%
“…47 Moreover, TA would aggrandize the crosslinking density of the gels, which could improve the steric stability for holding more water in the network. 48 In addition, the swelling ratio increased gradually with the TA content increases from 0.1 g up to 0.3 g, and then decreased considerably with further increases to 0.5 g. The maximum swelling ratio reached to 1179.2 g g −1 when TA content was 0.3 g. There is a possible reason that the proper amount of TA could increase the crosslinking density of gels so as to the swelling ratio increased gradually. However, the strongly cross-linked rigid structure obstructed network expansion of the gels in water with further increasing the TA content, it leaded to the decrease of the swelling rate.…”
Section: The Swelling Of Hydrogelmentioning
confidence: 87%
“…Agriculture is one of the major consumers of water, accounting for approximately 85% of utilization of available water resources [1]. Recent years have witnessed the ensuing effects of climate change, with water scarcity and associated desertification beginning to impact the agricultural sector.…”
Section: Introductionmentioning
confidence: 99%